2011
DOI: 10.1002/pssc.201084025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the capabilities and limitations of cathodoluminescence microscopy to investigate the optical properties of individual nanostructures

Abstract: Understanding the optical properties of individual semiconductor nanostructures is an important step in enabling novel optoelectronic components. The capabilities and limitations of cathodoluminescence microscopy in the scanning and scanning transmission electron microscope in correlating the physical and optical properties of quantum wells, wires and dots is evaluated. In particular the importance of specimen‐electron beam interactions and experimental conditions in maximising spatial resolution are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…An additional critical difference between EELS and CL is the mechanism of data acquisition. In CL, there are energy dissipation processes that occur in the beam-sample interaction volume, where excess carriers are regenerated, and it is the recombination of these carriers that generates each CL photon [49], while in EELS, the energy loss from the inelastic scattering events in the beam-sample volume is directly retrieved from changes in the same beam. This favors EELS not just in terms of spatial resolution accuracy but also in energy resolution [50].…”
Section: Exciting With Electrons and Probing With Photons (Cathodolummentioning
confidence: 99%
“…An additional critical difference between EELS and CL is the mechanism of data acquisition. In CL, there are energy dissipation processes that occur in the beam-sample interaction volume, where excess carriers are regenerated, and it is the recombination of these carriers that generates each CL photon [49], while in EELS, the energy loss from the inelastic scattering events in the beam-sample volume is directly retrieved from changes in the same beam. This favors EELS not just in terms of spatial resolution accuracy but also in energy resolution [50].…”
Section: Exciting With Electrons and Probing With Photons (Cathodolummentioning
confidence: 99%
“…Based on the range of defect emission energies, the Zn(Ac):KOH ratio appears to influence the density and size of zinc vacancy V Zn clusters [34]. Overall, multiple reviews of CLS applied to ZnO nanostructures are now available [35,36,37,38,39,40,41], and numerous studies have shown impurities and defects localized inside nanostructures [42,43,44,45,46].…”
Section: Defect Distributions In Znomentioning
confidence: 99%
“…73,74 Several comprehensive reviews of CLS applied to ZnO nanostructures are now available. 75,76,77,78,79 This chapter focuses on a very specific aspect of ZnO, i.e., the nature and spatiallyresolved distribution of defects at their interfaces and in particular inside their micro-and nanostructures. In general, defects in semiconductors have negative effects: they introduce states that can trap charge, increase non-radiative recombination, alter Schottky barriers and ohmic contacts.…”
Section: Introductionmentioning
confidence: 99%